Fast live-cell conventional fluorophore nanoscopy with ImageJ through super-resolution radial fluctuations - Nils Gustafsson (Nature Portfolio, 2016)
Super-resolution fluorescent imaging typically makes use of intense phototoxic illumination. Here the authors achieve live-cell super-resolution imaging using low-illumination standard microscopes with the aid of a new analytical approach called Super-Resolution Radial Fluctuations (SRRF), provided as an ImageJ plugin.